Culture your culture : innovating experiences @ work - Jaw-Madson, Karen (Emerald Publishing Limited, 2018)
Organizational culture isn't just a hot topic - it's an untapped asset and potential liability for all businesses. And yet, for all its potential to make or break, few know how to manage cultures with proficiency. Culture Your Culture: Innovating Experiences @Work provides the much-needed "how-to" with Design of Work Experience (DOWE). Tapping into human-centered design, interdisciplinary innovation concepts, and other research, this leading edge approach partners employees and their employers in unprecedented ways to co-create solutions and differentiating experiences that are customized, relevant, and profoundly impactful to the organizations for which they are intended - all while building employee engagement, learning agility, and capability. Be open to changing mindsets, for this is not your typical business book. Part-business case, part-instructional, and part-commentary, the guidance offered here puts your organization--not some detached case studies - at the center to envision how DOWE can help you design solutions and experiences unique to your context. Culture will no longer be esoteric or intangible, but overt, meaningful, fully leveraged, and truly experienced. No more hacking through trial and error to a culture that lacks sustainability. We can practice the management of culture and organizational change through lived experiences, with intention, rigor, and discipline. Leaders, managers, teams, and employees alike will benefit from understanding the need for this approach, how it's defined, why it works, and what to do to successfully tackle business challenges and positively influence lives with this innovative model if you are willing to do the work to get there.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Corporate culture; Organizational behavior; Diffusion of innovations; Business & Economics, Workplace Culture; Organizational theory & behaviour